REVIEW ARTIKEL: PEMANFAATAN LIMBAH TULANG AYAM SEBAGAI SUMBER KOLAGEN UNTUK ANTI AGING PADA KULIT - Eko Sri Wahyuningsih (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Aging is a natural process that occurs to every human being and is influenced by various factors from inside and outside the body. Aging can be caused by old age, insufficient nutritional intake, to the presence of free radicals in the skin. Aging can be prevented or slowed down with the use of sufficient, appropriate, and appropriate collagen. Collagen can be obtained naturally, one of which comes from chicken bones. This study uses the Literature Review Article method. By reviewing several articles or literature related to this theme, 5 types of articles, both national and international published in the last 10 years, are used. The literature obtained is an article found using the keywords Chicken bone as collagen source, chicken bone as a source of collagen, chicken bone waste for antiaging, and collagen for antiaging sourced from chicken bones. Based on the exposure, it is known that chicken bones can be an alternative source of collagen to be applied to cosmetics that can prevent or slow down aging of the skin.